MENUMBUHKAN SIKAP SALING MENGHARGAI DAN MENGHORMATI ANTAR SESAMA PADA ANAK DI YAYASAN PENDIDIKAN ISLAM ASHABUL MUHAJIRIN MEDAN - Hoki Diana Siregar; Mia Aulina Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Field work Practice (PKL) is learning that provides students with the opportunity to study outside campus for one semester. Through this PKL program, students Will be more active outside campus and hone their creativity for sustainability and improving the quality of Education. This journal Will explain the practical field work program carried out at the Ashabul Muhajirin Medan Islamic Foundation, which is located on Jl.Perjuangan No.45L,Tj.Rejo, Kec.Medan Sunggal, Medan City, North Sumatra 20122. The focus of this PKL program is to foster an attitude of mutual respect and respect among children.